2022
DOI: 10.3389/fcvm.2022.986039
|View full text |Cite
|
Sign up to set email alerts
|

Impact of levosimendan on efficacy and renal function in acute heart failure according to renal function: A perspective, multi-center, real-world registry

Abstract: ObjectiveAcute heart failure (AHF) is associated with high mortality. Levosimendan, an inodilator, has proved to increase cardiac output and exert renoprotective effect in AHF. Our aim was to investigate the efficacy and renoprotective effects of levosimendan in patients with AHF and different renal function.MethodsThis is a prospective, observational, multi-center registry. Patients admitted with AHF between June 2020 and May 2022 and treated with levosimendan during the hospital stay were included. Baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In comparison with levosimendan, dobutamine was found to be ineffective in patients receiving beta-blocker therapy [7]. Finally, a perspective, multi-center, real-world registry demonstrated that levosimendan infusion increased GFR only in acute heart failure patients with renal dysfunction [38].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with levosimendan, dobutamine was found to be ineffective in patients receiving beta-blocker therapy [7]. Finally, a perspective, multi-center, real-world registry demonstrated that levosimendan infusion increased GFR only in acute heart failure patients with renal dysfunction [38].…”
Section: Discussionmentioning
confidence: 99%
“…If a patient had documented CKD, it was defined as the lowest creatinine value during hospitalization [ 6 , 9 , 24 , 25 ]. Baseline glomerular filtration rates were calculated using the Modification of Diet in takes diseases equation estimation [ 26 ]. AKI was determined following the 2012 Kidney Disease: Improving Global Outcomes Clinical Practice Guidelines [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“… Levosimendan It was associated with a lower incidence of cardiorenal syndrome and better recovery of renal function at discharge, so Levosimendan appears to have some renoprotective effect and may be an effective and safe option in patients with advanced chronic kidney disease and heart failure. However, it is eliminated mainly by the kidneys, so the dose may need to be adjusted in these patients to avoid adverse effects and accumulation ( 100 , 101 ).…”
Section: Advanced Measures In Cardiorenal Patientsmentioning
confidence: 99%